A Study on UAE Courts Supervisory Powers in Arbitration on the Grounds of Public Policy Consideration - AL JELANI, MOHAMMED ANWAR (2017)
A comprehensive lineup of the problem and how important it is to tackle it: The Court of Cessation may overturn the arbitration award on the basis that the arbitration award conflicts the principal of “public policy. Since the definition of public order is an expanded one, in addition to the absence of a consistent measure of its' elements, all that will make it difficult for the disputing parties to determine whether they should proceed the arbitration path or court’s path, whereas a wrong decision will lead to a waste of time, money and the delay of rights. For these reasons, this dissertation will analyze different UAE Courts decisions, and I will try and mention as many examples as I can for public order to help litigants as well as arbitrators and the courts to base their decisions on the rationale and strong jurisprudence.